A context-specific circadian clock in adipocyte precursor cells modulates adipogenesis. (2nd October 2018) - Jung, Yunshin; Feldman, Brian J.
ABSTRACT: The circadian clock is an intricate molecular network that paces a variety of physiological process to ~ 24 hour day/night cycles. Whereas the central circadian clock in the brain is primarily entrained by light signals, peripheral circadian clocks, which are in most cells in the body, receive cues not only from the central pacemaker but also endocrine and other systemic and tissue-specific signals. Prior studies have connected peripheral circadian clocks to metabolism, primarily with studies focused on the robust clock in the liver that responds to feeding/fasting cycles. Adipose tissue is also critical for metabolism and adipocytes have circadian clocks. Yet, the role of the circadian clock in adipocytes is poorly understood. Here we describe our studies that revealed components of the circadian clock in primary adipocyte precursor cells (APCs) in mice. We made the surprising discovery of a particularly prominent role for the circadian gene Period 3 ( Per3 ) in the APC clock. Furthermore, we elucidated that Per3 directly regulates an output pathway of the APC clock to modulate the expression of the Kruppel-like factor 15 ( Klf15 ) gene. Finally, we discovered that this clock-Klf15 pathway regulates adipogenesis in APCs. These finding have important implications for our understanding of adipose tissue biology and metabolism and, we speculate, will generate opportunities to develop novel therapeutic strategies based on the context-specific features of the circadian clock in APCs.